ANALISIS HASIL VALIDITAS E-MODUL INTERAKTIF PADA MATERI IKLIM DAN PERUBAHANNYA UNTUK SISWA KELAS IV SEKOLAH DASAR - Awaliya, Nabila; Nurani, Dwi Cahaya; Susiloningsih, Esti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is an R&D research with the ADDIE model which aims to determine the validity or feasibility of the interactive e-module based on flipbooks on climate and its changes. The results of this study are that the feasibility validation by material experts is 90% "Very Valid". The validation by media experts obtained a percentage of 92.9% "Very Valid". The first teacher practitioner obtained a percentage of 97.5% "Very Valid" and the second teacher practitioner obtained a percentage of 97.5% "Very Valid". In total, the average percentage is 94.48%. Based on these results, it can be concluded that the interactive e-module based on flipbooks on climate and its changes is feasible to be tested on students.